PELATIHAN DESIGN AKSESORIS DI DESA KERINJING KABUPATEN OGAN ILIR SUMATERA SELATAN - putri, yulia hamdaini; Eka, Dian; Daud, Islahuddin; Tripermata, Lukita; Ramadani, Poni Fitria; Sari, Ratih Kurnia (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
Kerinjing Village is one of the villages located in Ogan Ilir Regency, South Sumatra. The majority of the villagers' livelihoods are farming rainfed rice fields. The rice fields are still natural, so for their daily activities they also have a side business. Apart from their main job, they have jobs as tailors. This service activity aims to provide training on how to make accessories designs from jumputan fabrics and how to pack. The method of this activity is providing counseling, training, providing equipment and accessories for making accessories to participants. The result of this service activity is that participants have increased skills in making accessory designs.